From clean up to FICAC: anti-corruption in Fiji’s post coup politics - Larmour, Peter (Crime, law and social change, 2010)
The leaders of Fiji’s 2006 military coup launched a ‘cleanup campaign’ and set up an Independent Commission Against Corruption. So far it has brought court cases against about 24 people. Among them is the former Prime Minister, who was charged with corruption for his role in institutions designed to promote the economic interests of indigenous Fijians (who constitute about 56% of the population). The article considers what counts as ‘corruption’ in these Affirmative Action policies: a so-called ‘Agriculture Scam’, which distributed farm implements free to Fijian farmers; a company called Fijian Holdings, which received concessional finance from the government; and a Native Land Trust Board, which collects rent on behalf of indigenous landowners. It concludes that army and popular opinion in Fiji hold conceptions of corruption that are much broader than the offences set out in the country’s penal code, and which the new ICAC is attempting to enforce.